THE ROLE OF ABDULKHOLIK GIJDUVANI’S “MAQAMOTI YUSUF HAMADONI” IN THE DEVELOPMENT OF YOUNG PEOPLE - Nurmatova , Nigora Umarovna (Educational Research in Universal Sciences, 2023)
In the article, it was spoken about Abdulkholiq Ghijduvoniy and there was analyzed his work “Maqamoti Yusuf Hamadoniy”, which he devoted to his master. This paper also draws attention to the fact that, along with giving valuable information about Yusuf Hamadoniy’s life and activities, there are some problematic information and the author’s own point of view about its reasons is given.